PENINGKATAN PENGETAHUAN IBU TENTANG PENCEGAHAN STUNTING - Yuswatiningsih, Endang; Suhariati, Hindyah Ike; Nofalia, Ifa; Oktopriana, Melinda; Wahida (JURNAL PENGABDIAN MASYARAKAT KESEHATAN (ABDIMAKES), 2023)
Children who are stunted will be more susceptible to infection which can increase the risk of decreasing the quality of learning in children. The purpose of this community service is to increase mothers' knowledge about stunting. The implementation of this community service is in the form of health education. This health education uses the lecture method and questions and answers about the material that has been delivered. The implementation of health education is based on the Health Education Program Unit which has previously been prepared. The contents consist of general goals and specific goals, targets, material/content, stages of counseling, activities of presenters and participants (mothers under five), media and tools for health education, and evaluation sheets. The target of this community service is mothers who are in Al-Husna Tembelang Jombang Islamic Kindergarten as many as 26 respondents. The results of this community service evaluation show that the knowledge of mothers about stunting before being given health education is mostly lacking and the knowledge of mothers about stunting after being given health education is mostly good. Increased knowledge is expected to encourage mothers to provide good nutrition to their children. The school is expected to be active in collaborating with health service agencies and health education to continue to work together to improve good intake patterns and be able to increase the enthusiasm for learning as well as the immunity of their students.